Compact asymmetric-cross slotted microstrip antenna on reactive impedance surface - Agarwal, Kush (2013)
A compact, asymmetric-cross slotted microstrip patch antenna on reactive impedance surface (RIS) is proposed and studied for the circularly polarized radiation. The circularly polarized radiation with compact size is achieved by an asymmetric cross slot cut along the orthogonal directions in the center of patch radiator over RIS. The measured results of the proposed antenna are 1.6% (2.51-2.55 GHz) for 3-dB axial ratio bandwidth, 5.2% (2.47-2.60 GHz) for 10-dB return loss bandwidth, and 3.4 dBic for gain at the boresight. The patch radiator size is 0.18 λo × 0.18 λo on a low cost FR4 substrate at 2.5 GHz.